2020
DOI: 10.2147/rmhp.s239984
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Syndromic Surveillance System for MERS-CoV as New Early Warning and Identification Approach</p>

Abstract: This commentary presents a novel outlook for public health authorities in the affected countries to detect and respond quickly to the emerging public health threats such as Middle East respiratory syndrome coronavirus (MERS-CoV). Implementing an innovative electronic surveillance system called syndromic surveillance system is essential for global health security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Although all ages are susceptible to catching the SARS-CoV-2, our results ( Table 1 ) consistent with previous reports, suggest that older people are more involved with the SARS-CoV-2 disease. This evidence and behavior of coronavirus as a large number of viruses that cause illnesses ranging from the mild common cold to severe pneumonia which is similar to MERS-CoV ( 15 - 20 ) has been confirmed in previously conducted studies ( 21 , 22 ). The authors of the study suggested that this issue be separately investigated in further study.…”
Section: Discussionsupporting
confidence: 77%
“…Although all ages are susceptible to catching the SARS-CoV-2, our results ( Table 1 ) consistent with previous reports, suggest that older people are more involved with the SARS-CoV-2 disease. This evidence and behavior of coronavirus as a large number of viruses that cause illnesses ranging from the mild common cold to severe pneumonia which is similar to MERS-CoV ( 15 - 20 ) has been confirmed in previously conducted studies ( 21 , 22 ). The authors of the study suggested that this issue be separately investigated in further study.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, countries on the South American plate with relatively young populations (i.e., Peru, Ecuador) have experienced severe COVID-19 outbreaks ( Accinelli and Leon-Abarca, 2020 ; Quevedo-Ramirez et al, 2020 ; Del Brutto et al, 2020 ). Although regions with weak health systems have a relatively lower molecular diagnostic capacity, syndromic surveillance is employed globally ( Daughton et al, 2020 ; Aghaali et al, 2020 ; Salamatbakhsh et al, 2020 ; Smith et al, 2020 ; Sokhna et al, 2020 ); thus, deaths due to an emerging, severe acute respiratory disease is captured uniformly across time and different countries, irrespective of national wealth ( Mbow et al, 2020 ). Tropical (warmer) climate per se does not affect the severity of the COVID-19 pandemic ( Xie and Zhu, 2020 ; Ascencio-Vasquez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Although coronaviruses have been mostly reported in animals, other types of coronavirus have caused pandemics of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) in the world within the past two decades. [2][3][4][5][6][7][8] The mortality rates of SARS and MERS were respectively reported at 10% and 37%, which are higher in comparison to COVID-19. 9,10 Symptoms of COVID-19 in 80% of infected people are mild, and common symptoms include, fever, dry cough and shortness of breath.…”
Section: Introductionmentioning
confidence: 93%